Event Study Analysis of The Covid-19 Outbreak On Stock Prices Listed on The Indonesia Stock Exchange - Jatmiko, Dadang Prasetyo (Adpebi International Journal of Multidisciplinary Sciences, 2022)
Purpose – This study aimed to examine the information content contained in the first event of the COVID-19 outbreak in Indonesia on March 2, 2020, by analysing abnormal return and stock trading volume activity in the tourism, transportation, textile, medical device, pharmaceutical and food and beverage sectors around the event Methodology/approach – This study used quantitative research with an event study approach. The samples were selected with purposive sampling as a sampling technique. The hypothesis test using the abnormal return indicators was carried out by conducting a statistical test of the average abnormal return for each event, while the hypothesis test using the trading volume activity indicators was carried out by conducting a paired-difference samples t-test by comparing the t-statistic value with the t-table value on the average trading volume activity before and after with the t-table value and 243 Latvian, 103 Estonian, and 109 Lithuanian entrepreneurs. Findings – The findings showed that when the first event of the COVID-19 outbreak occurred in Indonesia, there was a market reaction in the tourism, transportation, textile, medical device, pharmaceutical and food and beverage sectors. Novelty/value – The test result is important to show the difference test results of the two average trading volume activities during the first event of the COVID-19 outbreak in Indonesia showed that there was significant trading volume activity in the medical device and pharmaceutical sectors